Criminal legal aid and access to justice: an empirical account of a reduction in resilience. Issue 1 (2nd January 2022) - Dehaghani, Roxanna; Newman, Daniel
ABSTRACT: This paper examines the work of criminal legal aid solicitors and the state of practice under challenging conditions for the sector. Drawing on an empirical study in south Wales containing 20 semi-structured interviews, it provides original data on the frontline of criminal practice. It is argued – using vulnerability theory – that the challenges facing criminal legal aid solicitors deplete their and their client's resilience but at the same time bolsters the resilience of the police and prosecution. It further urges that vulnerability theory be used to examine criminal justice in practice, particularly the dynamics between various actors.